The Triassic turtle of Thailand - revision of 'Proganochelys' ruchae. - Tomasz Szczygielski; Dawid Dróżdż; Phornphen Chanthasit; Sita Manitkoon; Pitaksit Ditbanjong (PLoS ONE)
True turtles (Testudinata) appeared in the Norian (Late Triassic) and quickly attained a worldwide distribution and relatively high diversity. Their remains are currently known from that time from Asia, Europe, North America, and South America, and represent at least three separate clades. Whereas the generic and suprageneric attribution of comparatively well-preserved and studied European and South American taxa, such as Proganochelys quenstedtii, Proterochersis robusta and Proterochersis porebensis, Palaeochersis talampayensis, and Waluchelys cavitesta sparks no controversy, the more fragmentary and less common species have been variably considered representatives of separate genera or referred to already existing ones - most commonly, Proganochelys. This uncertainty is unfortunate, as it severely muddles the picture of the evolution, diversity, and geographical distribution of the earliest turtles. One such problematic species, coming from the Norian Huai Hin Lat Formation of Thailand, was described in 1980s as Proganochelys ruchae. However, this generic attribution was subsequently put into question and the recent increase of available Triassic turtle material allows to remove the species ruchae from Proganochelys to a new genus, Thaichelys gen. nov., and place it in the clade of Proterochersidae, together with Proterochersis spp., Keuperotesta limendorsa, and Chinlechelys tenertesta. As a result, the genus Proganochelys is considered here to be solely a central Pangean (modern-day European) taxon. Moreover, Thaichelys ruchae exhibits in some respects a transitional morphology between other Triassic taxa and Proterochersis spp., and may constitute a sister taxon to the grouping of Proterochersis spp. and Keuperotesta limendorsa from Europe. This, in turn, considering the lack of a Carnian record of pantestudinates outside of Asia, suggests that Thaichelys ruchae could represent an early radiation of the Proterochersidae which branched off before the Testudinata dispersed into the western Pangea.